Case Report of An Unusual Mediastinal Mass - Thymolipoma - Raju, Sreeja; S, Divya; Savithri, M C; KK, Ajaykumar; Nair, Gayathri G (Annals of Pathology and Laboratory Medicine, 2020)
Thymolipomas are rare, slow-growing, benign anterior mediastinal neoplasms which are very often detected incidentally. Here we present a case of a 47 year old female who presented with chest discomfort and radiology revealed an anterior mediastinal mass. Total thymectomy was done and histopathology showed features consistent with thymolipoma. Very few cases of thymolipomas have been reported in Indian and world literature.